ATF1 and miR-27b-3p drive intervertebral disc degeneration through the PPARG/NF-κB signaling axis - Wei Guo; Kun Mu; Jing-Chao Geng; Hai-Yang Xing; Yu Dong; Wen-Dong Liu; Shuan-Chi Wang; Jia-Xiao Shi; Bao-Rui Xing; Jian-Yong Zhao; Xiao-Ming Li (Communications Biology)
Abstract Intervertebral disc degeneration (IDD) is a primary cause of degenerative disc disease; however, the mechanisms underlying it remain unknown. Although great efforts have been made to develop new regenerative therapies, their clinical success is limited. Recent research has indicated that microRNAs (miRNAs) are significantly involved in the progression of IDD. Investigating the role of miRNA intervention in IDD could facilitate the development of therapeutic strategies based on miRNAs. However, circulating miRNAs have not yet been recognized as standard biomarkers for IDD. In this study, we observed that the expression of miR-27b-3p was elevated in the blood and nucleus pulposus (NP) tissue of patients with IDD. Furthermore, reducing the expression of miR-27b-3p was shown to impede the progression of IDD. MiR-27b-3p could reduce the expression of collagen II and ACAN and promote the expression of MMP13 and ADAMT-5 in vitro and in vivo. miR-27b-3p aggravated IDD progression by directly targeting peroxisome proliferator-activated receptor gamma (PPARG), a negative regulator of the NF-κB signal pathway. This study also established that PPARG serves a protective role in IDD. The overexpression of PPARG was able to mitigate the detrimental effects caused by miR-27b-3p in NP cells and animal models of IDD, indicating that miR-27b-3p facilitates the progression of IDD through its interaction with PPARG. Additionally, the transcription factor ATF1 was found to enhance the expression of miR-27b-3p by targeting its promoter region, thereby promoting the degenerative impact of miR-27b-3p on NP cells. Given that miR-27b-3p can promote IDD both in vitro and in vivo, it holds potential as a biomarker, and the inhibition of miR-27b-3p expression may represent a novel therapeutic target for IDD.